Pembinaan Pembuatan Mainan Edukatif Anak Berbahan Pinalo dengan Desain Digital Ramah Lingkungan - Agustina, Ahadiah; Suhairin; Ageska Nugroho; Baiq Andini (BALE LITERASI, 2026)
This Community Service Program aims to improve community creativity and skills in producing educational toys for children using pinalo-based environmentally friendly digital design approaches. The program was motivated by the limited utilization of local eco-friendly materials as educational media for children and the lack of community competence in developing creative products through digital design technology. The program employed a Participatory Action Research (PAR) approach through several stages, including needs assessment, digital design training, educational toy workshops, production assistance, and program evaluation. The educational toys produced included alphabet puzzles, educational blocks, counting games, and color recognition media made from pinalo materials designed using simple digital applications. The results showed an improvement in participants’ skills in transforming local materials into educational products with economic value and environmental sustainability. Furthermore, participants demonstrated enhanced competence in utilizing digital design for creative product development. This program contributes to the development of environmentally based creative industries and supports children’s learning through safe and eco-friendly educational toys.